А) (х + 3)(х – 2) - (х + 4)(х – 1) = 3х, б) (2х + 6)(7 – 4х) = (2 – х)(8х + 1) + 15,

в) (х - 4)(х + 2) - (х - 5)(х + 6) = - х,

г) (3х + 5)(2х + 1) = (6х + 5)(х - 3) + 7.

jdgdjrs jdgdjrs    2   25.11.2021 07:53    0

Ответы
Rustam7887 Rustam7887  25.11.2021 08:00

(х+3)(х-2)-(х+4)(х-1)=3х

(х^2-2x+3x-6)-(x^2-x+4x-4)=3x

x^2+x-6-(x^2+3x-4)=3x

x^2+x-6-x^2-3x+4-3x=0

x-6-3x+4-3x=0

-5x-2=0

-5x=2

х=2/-5

х=-0,4

ответ: -0,4.

это первое дальше нужно думать самим сори(

Пошаговое объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика